2017
DOI: 10.1007/s11655-017-2965-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shen-Fu Injection (参附注射液) on Hemodynamics in Early Volume Resuscitation Treated Septic Shock Patients

Abstract: SFI significantly improved hemodynamic indices such as CI, GEDI, MAP and HR in early volume resuscitation treated septic shock patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Secondly, SF injection has been reported to play a protective role in blood vessel spasm and microcirculation. Additionally, the components of SF, ginsenosides and aconitine, exert significantly protective effect on cardiovascular system by activating α and β receptors, thereby enhancing cardiac function as well as elevating and stabilizing blood pressure to relieve reperfusion injury [ 24 ] . However, inflammatory markers and related measurements were not investigated, and this was the limitation in our study; further studies on the abovementioned process should be focused on these.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, SF injection has been reported to play a protective role in blood vessel spasm and microcirculation. Additionally, the components of SF, ginsenosides and aconitine, exert significantly protective effect on cardiovascular system by activating α and β receptors, thereby enhancing cardiac function as well as elevating and stabilizing blood pressure to relieve reperfusion injury [ 24 ] . However, inflammatory markers and related measurements were not investigated, and this was the limitation in our study; further studies on the abovementioned process should be focused on these.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this strategy, the combination of SF with standard bundle therapy significantly improved patients' circulation, tissue perfusion, and coagulation function, as well as inflammation reactions [69]. Adding SF to conventional therapy could increase patients' mean arterial pressure (MAP), normalize the heart rate, clear serum lactate, and reduce the mortality of patients, thus reducing the occurrence of septic shock and the need for resuscitation [70,71]. Based on a systematic review and meta-analysis of randomized controlled trials, compared with standard therapy, the addition of SF showed a trend of decreasing 28-day mortality (p = 0.17) only for the septic shock patients, with 4.5 mmol/L ≤ mean arterial lactate level < 7 mmol/L and with a yang-qi deficiency (a TCM syndrome) [72].…”
Section: Shenfu Injectionmentioning
confidence: 99%
“…[ 59 ] It could improve the survival rate of endotoxin shock in a rat model of acute lung injury through inhibiting the HMGB1-NF-κB pathway and preventing cytokine storm. [ 60 ] In addition, ShenFu injection (Ya'an San-jiu Pharmaceutical Co., LTD., Sichuan, China) with the dosage of 100 mL (12 hours a day, intravenous drip) also significantly improved hemodynamic indices such as cardiac index, global end diastolic volume index, mean arterial pressure, and heart rate, in early volume resuscitation treated septic shock patients.. [ 61 ] Combined metabolic pathway enrichment and topology analyses indicated that the mechanisms of ShenFu injection against coxsackievirus B3-induced acute viral myocarditis might be due to modulating the disordered homeostasis of sphingolipid metabolism, arachidonic acid metabolism, glycerophospholipid metabolism, tryptophan metabolism, and TCA cycle. [ 62 ] In vivo work showed that ShenFu injection not only inhibited NF-κB activity, but also reduced TNF-α and IL-6 expressions in systemic inflammatory response syndrome rats.…”
Section: Chinese Herbal Injections For Covid-19mentioning
confidence: 99%